Improvement of Matrinxã, Brycon amazonicus, Larviculture by Exposing Eggs to Triiodothyronine - Leonardo, Antonio Fernando Gervásio; Hoshiba, Márcio Aquio [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP]; Senhorini, José Augusto (Wiley, 2013)
This work evaluated the effect of triiodothyronine (T3) on larviculture of matrinxã, Brycon amazonicus. Oocytes of three females were pooled, fertilized with pooled semen of two males and separated in four batches that were immersed in triiodothyronine solutions as follows: M1 (control - water); M2 (0.01mg/L T3); M3 (0.05mg/L T3); and M4 (0.1mg/L T3). Triiodothyronine did not affect fertilization rate and number of hatched larvae. Weight of hatched larvae was significantly higher in treatments M3 and M4, as well as among larvae sampled at Day 12 in all treatments. After 12d of rearing, biomass gain was higher in the hormone treatments (M1 688±569mg; M2 2436±562mg; M3 3572±569mg; and M4 4129±770mg). In general, coefficients of variation of weight (CVw) and length (CVl) did not differ among treatments and cannibalism was registered between 36 and 72hours post-hatching (h.p.h.) without differences among treatments. Larval survival increased in the hormone treatments (M1 26.5%; M2 37.6%; M3 40.6%; and M4 40.8%). The results indicate that the immersion of matrinxã eggs in triiodothyronine can promote beneficial effects to its larviculture and indicate promising perspectives for culture of this tropical species. © by the World Aquaculture Society 2013.
Keywords: biomass; cannibalism; egg development; fertilization (reproduction); fish culture; hormone; larva; larviculture; rearing; survival